A Proposed Strategy for Managing the Environmental Hazards of Wind Energy Projects in Jebel El-Zeit - Ahmed, Nefesa Hassan; Mohamed, Abu Bakr Abd ElHameed; Ibrahim, Wed Abd-El Latif; El-Shahaat, Nehal Fathy (The Arab Journal of Administration, 2025)
This research aims to study the impact of proposed strategic dimensions on reducing the environmental risks of Wind projects on migratory birds in the Jabal al-Zayt area in light of activating the role of environmental project management system. This is a continuation of the research carried out by the researchers and published under the title “The Impact of Activating the Role of Environmental Management on Reducing the Risks to Migratory Birds in the Gabal El-Zeit Region in Egypt.” The research objectives were achieved through: Designing a questionnaire to collect data and distributed to a sample of (120) person from project site workers, experts, academics, government officials, and civil society to study the effect of activating environmental management and the dimensions of the proposed strategy to reduce these risks. To check the validity of the research hypotheses, the researcher used some statistical methods were represented in means, standard deviations, and progressive multiple regression analysis and analysis path program Amos. And based on the results of the previous research, which identified the types of risks to which migratory birds are exposed, the researchers conducted this research to develop a strategy to conserve and protect migratory birds in the presence of dimensions of environmental management as a mediating variable to reduce the environmental risks of wind energy projects. The study reached the following results: There is an effect of the dimensions of the risk management strategy combined on the environmental risks by 71.7%, and that environmental management as an intermediate variable (Mediator Variable) qualifies the direct effect of Environmental Risk Management Strategy on environmental hazards. The study recommends strengthening the role of periodic environmental monitoring of projects, maximizing the benefit of the state’s interest in applying environmental sustainability standards to increase coordination and cooperation between the concerned authorities to develop standards for preserving biological diversity, developing policies and procedures that guarantee coordination between the concerned government agencies in this regard and working on sustainable development planning for the region, developing an environmental management system in accordance with ISO 14001.